EVALUATION OF THE IMPLEMENTATION OF CATALYST SCHOOL SD PANCA BHAKTI IN KECAMATAN MAKASAR JAKARTA TIMUR - SETIYOWATI, Ari (Journal of Education and Leadership in Education, 2024)
This study evaluated the Implementation of the Catalyst Schools Program at SD Panca Bhakti, Makassar District, East Jakarta, using the Stake evaluation model. The purpose of this study is to identify the effectiveness of the program in improving the quality of education and identify supporting and inhibiting factors in its implementation. The methods used are qualitative methods with Case Study approaches, Phenomenology and descriptive investigation. Data was collected through in-depth interviews, observations, and document analysis. The results of the study show that the implementation of the Catalyst Schools Program at SD Panca Bhakti Makassar District, East Jakarta has had a positive impact on increasing student learning motivation and learning quality. And the improvement in the quality of Education can be seen from the Education Quality Report Card. Where there is an increase in value every year. However, there are several obstacles that need to be overcome, such as the limitations of facilities and infrastructure, as well as the understanding that is still diverse among teachers regarding the new curriculum. Based on antecedent, transaction, and outcomes evaluations, recommendations are given to improve and improve the implementation of this program in the future. This research is expected to be a guideline to improve the quality of Catalyst Schools at SD Panca Bhakti, Makassar District, East Jakarta, in particular and surrounding schools in general, with an emphasis on improving human resource management, increasing the use of learning media, and adjusting learning methods.